(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
A wide array of energy storage technologies exists, encompassing mechanical, thermal, electrostatic, chemical, and electrochemical processes. Energy storage systems (ESS) can be integrated with renewable energy sources to enhance system flexibility as well as comply to grid restrictions. The selection of an appropriate technology depends on various project-specific factors, including availability, maturity, geographical conditions, space constraints, safety constraints and attentions, raw material availability, deployment time, and acceptable CAPEX. Key parameters to evaluate include energy density, energy/power ratio, expected lifetime, safety risks, and mitigation strategies. In Blue Economy projects, the location and site conditions also significantly influence the choice of ESS. To illustrate it, a return on experience based on the FORWARD2030 EU project will be used (Grant agreement ID: 101037125, funded by the European Commission), where ENGIE Laborelec is a partner. One of the Project’s goals is to demonstrate the feasibility of a zero-carbon energy system that combines wind and tidal energy with energy storage solutions. To minimize energy curtailment through dynamic limitation, simulations were conducted to assess the impact of integrating an ESS to enhance tidal energy grid injection potential. The results indicated that optimal performance given the site and project specificities would be achieved by coupling tidal energy with a 1MW/1MWh storage solution, requiring a minimum of 236 cycles per year. But these are the dimensions of the ESS not the type of ESS technology. To select the specific technology, we considered market availability, safety aspects, and Technology Readiness Level (TRL) to ensure feasible installation and operation within the project’s timeframe. Furthermore, special attention was given to the safety aspects including an overview of the main hazards associated with offshore energy projects, as well as a review of relevant safety standards and best practices. To further illustrate the safety aspects, a comprehensive overview of the safety considerations for lithium-ion batteries will be shared. Lithium-ion batteries, while highly efficient and widely used, present specific hazards that must be carefully managed. One of the critical safety concerns of this technology is thermal runaway, a self-sustaining reaction where the battery overheats and potentially catch fire or explode. This process can be triggered by various factors, including overcharging, physical damage, etc. To mitigate these risks, several strategies are employed, focusing on material selection, integration, and installation. Additionally, the safety assessment for lithium-ion batteries involves evaluating their compliance with international safety standards, which outline requirements for the safe operation of battery systems. Best practices in installation, operation, and maintenance are also considered to ensure long-term safety and reliability. By addressing these safety considerations, the project aims to ensure that the integration of lithium-ion batteries into Blue Economy projects is both effective and secure. This supports the overall goal of demonstrating a viable zero-carbon energy system.